Developing Health Communication Materials During a Pandemic - Benski, Caroline; Goto, Aya; , Creative Health Teams; Reich, Michael R. (Frontiers in Communication, 2020)
Background: The COVID-19 pandemic produced a massive amount of information all around the world. A major public health challenge is to deliver health communication products with clear and simple messages during a health crisis and to reach all audiences, especially vulnerable populations. Objectives: We compared and analyzed the development processes of health communication products for pregnant women in Madagascar and for elementary school children in Japan during the COVID-19 pandemic. Methods: This study compared these two field experiences in different socioeconomic settings to identify common strategies for the development of communication materials in a health crisis. Results: The two cases developed communication materials in collaboration with key local communicators and the target audiences. Both products used a simple and clear structure and included do’s and don’ts. Messages were tailored toward the lifestyles of the target audience and phrased to fit with cultural and linguistic contexts. Both developer teams paid attention to easy-to-understand words and culturally accepted design and colors. Conclusions: These two field experiences demonstrate common strategies for developing health communication materials that are culturally-tailored and visually-appealing in a timely manner and can be disseminated through existing channels in a health crisis. Our experiences emphasize that collaborative and iterative efforts based on an existing trust relationship with the target community can provide the foundation for a rapid communication response in a health crisis.